Chronic depressive symptomatology and CSF amyloid beta and tau levels in mild cognitive impairment. (28th June 2018) - Gonzales, Mitzi M.; Insel, Philip S.; Nelson, Craig; Tosun, Duygu; Schöll, Michael; Mattsson, Niklas; Sacuiu, Simona; Bickford, David; Weiner, Michael W.; Mackin, R. Scott
Abstract : Objectives: To investigate the association between chronic subsyndromal symptoms of depression (SSD), cerebrospinal fluid (CSF) biomarkers, and neuropsychological performance in individuals with mild cognitive impairment (MCI). Methods: Participants included 238 older adults diagnosed with MCI from the Alzheimer's Disease Neuroimaging Initiative repository with cognitive and CSF amyloid beta (Aβ1–42 ), total tau (t‐tau), and phosphorylated tau (p‐tau) data. The Neuropsychiatric Inventory identified individuals with chronic endorsement (SSD group N = 80) or no endorsement (non‐SSD group N = 158) of depressive symptoms across timepoints. CSF biomarker and cognitive performance were evaluated with linear regression models adjusting for age, education, gender, APOE genotype, global cognitive status, and SSD group. Results: As compared to the non‐SSD group, the SSD group displayed lower CSF Aβ1–42 levels (β = −24.293, S.E. = 6.345, P < 0.001). No group differences were observed for CSF t‐tau ( P = 0.497) or p‐tau levels ( P = 0.392). Lower CSF Aβ1–42 levels were associated with poorer performance on learning (β = 0.041, S.E. = 0.018, P = 0.021) and memory (β = −0.012, S.E. = 0.005, P = 0.031) measures, whereas higher CSF t‐tau levels were associated with poorer performance on measures of global cognition (β = 0.022, S.E = 0.008, P = 0.007) and language (β = −0.010, S.E = 0.004, P = 0.019). SSD was independently associated with diminished global cognition, learning and memory, language, and executive function performance over and above the effects of CSF biomarkers (all P < 0.05). Conclusions: MCI participants with SSD displayed diminished CSF Aβ1–42 levels but did not differ from non‐SSD controls in CSF tau levels. Additionally, CSF biomarkers and SSD independently accounted for variance in cognitive performance, suggesting that these factors may uniquely confer cognitive risk in MCI.